Delik Samen Leven Dalam KUHP Baru Perspektif Fikih - Multazam, Syauqi; Mujab, M. (Syariah: Journal of Fiqh Studies, 2023)
The creation of the law on the offense of the samen leven (cohabitation) in the new Criminal Code has reaped the pros and cons of society. Some support it, while others reject it on the grounds that the government is taking too much care of its citizens' privacy rights. Through this writing, the author wishes to analyze the creation of cohabitation offense laws from an Islamic perspective using a tool called fiqh. The research method used in this study was library research. The primary arguments in formulating Islamic views through this research are (1) Al-Qur'an, (2) Al-Hadith, (3) rules of jurisprudence and (4) at-turāṡ (yellow book). These primary postulates were then managed using a tafsīr (interpretation) approach to formulate the final conclusion. As a result of this research, the author found that from an Islamic perspective, the adoption of cohabitation as a law is in line with Islamic norms. However, jurisprudence does not necessarily agree with the content of articles of the law on cohabitation. Some articles are not in accordance with Islamic values. Therefore, in this case, the governent has an obligation to improve the content of the Samen Leven (cohabitation) Law.